Development of Contextual-Based Interactive Learning Videos Assisted by Edpuzzle on Electrolyte and Non-Electrolyte Solution Materials - Sihombing, Tioliska Mawar; Rusdi, M.; Afrida, Afrida (LPPPI Publishing, 2025)
Education is one of the keys to the progress of a country and nation. Because education is a driver of improving the quality of human resources in order to be able to compete in the increasingly sophisticated competition of national life. Therefore, educational institutions must be able to carry out a more quality learning process. The rapid development of technology requires educators to be able to integrate technology in the learning process. The purpose of this study is to determine the feasibility, practicality and effectiveness of the use of contextual-based interactive learning videos assisted by edpuzzle on electrolyte and non-electrolyte solution materials. This research targets the problems that occur in SMA 11 Muaro Jambi Class XII Phase F. This research is a type of development research with the Lee & Owens model which consists of 5 stages (analysis, design, development, implementation and evaluation). Validation from material experts achieved an average score (93.33%), material validation achieved results (95%), teacher assessment questionnaire as practitioners reached (100%), and student assessment questionnaire reached (95.45%) with Very Practical criteria and (96%) with very effective criteria. The results of the study show that the use of contextual-based learning videos assisted by edpuzzle is feasible, practical and effective to be used as a teaching medium.